Dose - response relationship between noise exposure and the risk of occupational injury - Jin-Ha Yoon (Noise and Health, 2015)
Many workers worldwide experience fatality and disability caused by occupational injuries. This study examined the relationship between noise exposure and occupational injuries at factories in Korea. A total of 1790 factories located in northern Gyeonggi Province, Korea was evaluated. The time-weighted average levels of dust and noise exposure were taken from Workplace Exposure Assessment data. Apart occupational injuries, sports events, traffic accidents, and other accidents occurring outside workplaces were excluded. The incidences of occupational injury in each factory were calculated by data from the Korea Workers′ Compensation and Welfare Services. Workplaces were classified according to the incidence of any occupational injuries (incident or nonincident workplaces, respectively). Workplace dust exposure was classified as <1 or ≥1 mg/m 3 , and noise exposure as <80, 80-89, or >90 dB. Workplaces with high noise exposure were significantly associated with being incident workplaces, whereas workplaces with high dust exposure were not. The odds ratios (95% confidence intervals) derived from a logistic regression model were 1.68 (1.27-2.24) and 3.42 (2.26-5.17) at 80-89 dB and ≥90 dB versus <80 dB. These associations remained significant when in a separate analysis according to high or low dust exposure level. Noise exposure increases the risk of occupational injury in the workplace. Furthermore, the risk of occupational injury increases with noise exposure level in a dose-response relationship. Therefore, strategies for reducing noise exposure level are required to decrease the risk of occupational injury.